Sono-urethrography in the evaluation of male anterior urethral strictures - Alam, A K M K; Hossain, M S; Faruque, M S; Siddique, F H; Hossain, M M; Amanullah, A T M; Shameem, I A; Chowdhury, G M; Joarder, M A I; Rahman, S M; et al. (Bangladesh Journal of Urology, 2012)
Objective: To evaluate the accurate length, site, number of male anterior urethral stricture and to determine the extent of spongiofibrosis by sonourethrography and comparing it with retrograde urethrogam and operative findings. Methods: This cross sectional study was conducted to evaluate 60 patients with anterior urethral stricture. All patients underwent retrograde urethrography (RGU) followed by sonourethrography (SUG) to evaluate abnormalities of male anterior urethra. All sonographic studies were performed with a standard ultrasound scanner (Just Vision 400, Toshiba) using a 7.5 MHz linear array transducer. With the patients in supine position anterior urethra was filled with saline and multiple longitudinal and transverse scans were taken. All cases underwent operative treatment. During operation all patients observed for length of stricture and degree of spongiofibrosis of stricture and correlated it with RGU & SUG findings. Results: The Mean (± SD) age of the patients of this study was 30.75 ±8.70 years and the age range of the subjects was 50 to 18 years. Sensitivity of SUG to diagnose urethral stricture length at cut off level 10 mm was 94.1%, specificity 97.7%, positive predictive value 94.1%, negative predictive value 97.7% and accuracy 96.7% (Kappa value = 0.918; p value <0.001). Sensitivity of RGU to diagnose urethral stricture length at cut off level 10 mm was 88.2%, specificity 86.0%, positive predictive value 71.4%, negative predictive value 94.9% and accuracy 86.7% (Kappa value = 0.693; p value <0.001). Diagnostic accuracy was determined as receiver operating characteristic (ROC) curve, suggesting that the area under the curve (AUC) of SUG and RUG was 0.959 and 0.871, respectively in the diagnosis of length of stricture (Fig.-1). Conclusion: Retrograde urethrography and sonourethrography are equally efficacious in detection of anterior urethral strictures. BJU 2010; 13(2): 51-56